Real-world evidence on tagraxofusp for blastic plasmacytoid dendritic cell neoplasm – collected cases from a single center and case reports - Faustmann, Philipp; Schroeder, Jan C.; Mix, Lucas; Harland, Lennart; Riedel, Andreas; Vogel, Wichard; Lengerke, Claudia; Wirths, Stefan (Frontiers in Oncology, 2024)
Blastic plasmacytoid dendritic cell neoplasia (BPDCN) is a rare, aggressive hematologic malig-nancy. Until recently, the only curative treatment consisted of intensive chemotherapy, followed by hematopoietic cell transplantation (HCT) in eligible adult cases. Tagraxofusp, a CD123-targeted protein-drug conjugate and the first approved targeted treatment for BPDCN, might enhance outcomes especially in patients not eligible for intensive therapies. Here, we report real-world outcomes of five male patients with a median age of 79 years who received tagraxofusp as first-line treatment for BPDCN. Tagraxofusp was found to be well-tolerated in this elderly cohort, with only one patient requiring discontinuation. Three patients responded to the treatment (two patients achieved a CR and one patient achieved a partial response), of which two subsequently underwent allogeneic (allo) HCT. One patient is alive and well after ≥ 4 years after alloHCT, and one patient shows sustained CR after now 13 cycles of tagraxofusp. The other three patients died of progressive disease 4-11 months after initiation of treatment. In line with results from 13 published cases outside clinical trials in the literature, sustained responses were associated with CR after tagraxofusp treatment and subsequent alloHCT. Our results provide real-world evidence for safety and efficacy of tagraxofusp as first-line treatment for BPDCN.